Remarkably enhanced performance of the metathesis reaction of ethylene and 1-butene to propene using one-step prepared W-MCM-41 catalysts. Issue 69 (9th December 2019) - Wang, Changji; Jiang, Feng; Zuo, Guangzheng; Liu, Bing; Li, Hanxu; Liu, Xiaohao
Abstract : The W-MCM-41 catalysts synthesized via one-step precipitation method showed the excellent activity and selectivity for the metathesis reaction of ethylene and 1-butene to propene. Abstract : Highly dispersed tungsten species with an isolated tetrahedral WO x species structure are substantially beneficial for the metathesis reaction of ethylene and 1-butene to propene. The conventional impregnation method always leads to the formation of inactive crystalline WO3 thereby notably decreasing the amount of active sites. In this study, we synthesized a highly dispersed W-MCM-41 catalyst using the one-step precipitation method with a Si/W ratio of 30. The prepared catalyst showed excellent catalytic performance with a 1-butene conversion of 92.7% and a propene selectivity of 80.8%. In contrast, the impregnated catalyst with the same W loading as the one-step precipitation method resulted in a much lower 1-butene conversion of 76.5% and propene selectivity of 34.1%. Various characterization techniques including XRD, XPS, ICP-OES, UV-vis DRS, TEM, and Raman spectroscopy were applied to confirm that the one-step precipitation method can efficiently prepare well-dispersed W-MCM-41 catalysts with the desired structure in spite of the fact that the ideal dispersive structure was strongly dependent of the Si/W ratio and stirring time of the reaction mixture of tungstic acid and TEOS. In addition, the introduction of an upstream catalyst onto the W-MCM-41 catalyst could not obviously improve the 1-butene conversion and propene selectivity, which might be due to fast 1-butene isomerization easily occurring on the abundant Si–OH of the W-MCM-41 catalyst. This work provides new insights for the design of metathesis catalysts and reaction processes to efficiently convert ethylene and 1-butene into propene.